English Result - Hancock, MArk; Annie, Macdonald (New York Oxford university press, 2008)
Student̓s Book
Pre-intermediate
The book take you in a tour with picture and active lessons to show you how to lessons provide a clear focus and practical Language outcomes
Audio scripts
12
Keywords: English Language -- Grammmar; English Language -- Idioms; English Language -- Part of speech; English Language -- Study guide; English Language -- Usage; English as a second Language